2011
DOI: 10.2174/156652411796268740
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid (DHA) Sensitizes Brain Tumor Cells to Etoposide-Induced Apoptosis

Abstract: In this study, we investigated whether DHA, a nutritionally important n-3 unsaturated fatty acid, modulated the sensitivity of brain tumor cells to the anticancer drug, etoposide (VP16). Medulloblastoma (MB) cell lines, Daoy and D283, and glioblastoma (GBM) cell lines, U138 and U87, were exposed to DHA or VP16 alone or in combination. The effects on cell proliferation and the induction of apoptosis were determined by using MTS and Hoechest 33342/PI double staining. U87 and U138 cells were found to be insensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…We made similar observations: 25-75 μM DHA diminished the proliferation rate and altered the metabolism of U87 MG cells (Figure 2). DHA treatment had a distinct effect on medulloblastoma (DAOY and D283) cells compared to glioma cells (U87 MG and U138) regarding cell proliferation: it did not affect glioma cells, while it inhibited proliferation of medulloblastoma cells [29]. …”
Section: Discussionmentioning
confidence: 99%
“…We made similar observations: 25-75 μM DHA diminished the proliferation rate and altered the metabolism of U87 MG cells (Figure 2). DHA treatment had a distinct effect on medulloblastoma (DAOY and D283) cells compared to glioma cells (U87 MG and U138) regarding cell proliferation: it did not affect glioma cells, while it inhibited proliferation of medulloblastoma cells [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Many of these interactions, such as those with the epidermal growth factor receptor, Src kinases, the Ras/Raf/MAPK pathway, PKCs and endothelial nitric oxide synthase (eNOS), occur via the scaffolding domain of Caveolin-1 (CSD; amino acids [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101] and the scaffolding domain binding domain (CBD) found in the respective target proteins [3]. However, as highlighted in Fig.…”
Section: Caveolin-1-mediated Control In Signalingmentioning
confidence: 99%
“…More recently, work from our group has shown that expression of the Inhibitor of Apoptosis (IAP) protein Survivin and also cyclooxygenase-2 (COX-2) are down-regulated by Caveolin-1 in a -catenin-Tcf/Lefdependent manner [81][82]. Interestingly, reduction of survivin expression has been associated with enhanced sensitivity to anti-cancer drugs [84].…”
Section: Mechanisms Of Transcriptional Controlmentioning
confidence: 99%
“…Wang et al combined the use of DHA with the anticancer drug etoposide (VP16) to induce apoptosis in medulloblastoma cell lines, Daoy and D283, and glioblastoma cell lines, U87 and U138. 44 U87 and U138 cell lines were insensitive to pretreatment with DHA followed by VP16 administration, whereas Daoy and D283 cells showed little responsiveness to either treatment alone, but a significant induction of apoptosis was observed with the combination. Wang's evidence suggests that the apoptosis mechanism involves the downregulation of survival pathways associated with DNA repair and PI3K/MAPK.…”
mentioning
confidence: 94%